Isolation, Identification and Medium Optimization for Tyrosinase Production by a Newly Isolated Bacillus subtilis NA2 Strain - Elsayed Ahmed Elsayed & , Enas Nabil Danial & (Journal of Applied Pharmaceutical Science, 2018)
Tyrosinase (EC 1.14.18.1, monophenol, O-diphenol: oxygen oxidoreductase) is a copper-metallo-bifunctional enzyme, which catalyzes the O-hydroxylation and oxidation of monophenols to quinones. Tyrosinase plays an important role in the immune defense mechanisms of many prokaryotic and eukaryotic organisms. It also finds many applications in antioxidants and therapeutic fields. In the present work, a newly isolated tyrosinase-producing strain (Bacillus subtilis NA2) was identified using 16S rDNA and BLAST analysis. The primary cultivation medium produced tyrosinase at 416.67 U/min/mL with a yield coefficient (YP/X) of 111.75 × 103 U/g cells. Furthermore, the cultivation medium for the production of tyrosinase was optimized. The final optimized cultivation medium composed of (g/L): sucrose, 10; KNO3, 10; K2HPO4, 0.5; MgSO4.7H2O, 0.25; tyrosine, 10 and the initial optimized pH of the cultivation medium was 8.5. It has been shown, that the final optimized medium with the optimized pH resulted in an increase of about 39% in tyrosinase production from the initial un-optimized conditions. The new tyrosinase producing strain was identified and its volumetric production was significantly increased after the successful optimization of the production medium.
Keywords: Isolation, Identification, Bacillus, Tyrosinase, Production, Yield coefficient.